ABOUT SYSTEM OF DISTANCE LEARNING IN OPEN ONLINE COURSE (Journal of Information Technologies in Education (ITE), 2012)
This paper describes the first part of the open online course "E-Learning from A to Z", dedicated to the creation and development of system of distance learning (university or corporation). The results of the learning process and discussion on the workshop at NTU "KPI" in 2012 is shown the interest of teachers in a new form of online course and lack of development of personal learning environment. The open online courses can contribute to society practice.
Keywords: connectivism; e-learning; social services; system of distance learning; the massive open online course